2020
DOI: 10.3390/ijms21030739
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Reconstituted High-Density Lipoprotein Nanoparticles in Cardiovascular Disease: A New Paradigm for Drug Discovery

Abstract: Epidemiological results revealed that there is an inverse correlation between high-density lipoprotein (HDL) cholesterol levels and risks of atherosclerotic cardiovascular disease (ASCVD). Mounting evidence supports that HDLs are atheroprotective, therefore, many therapeutic approaches have been developed to increase HDL cholesterol (HDL-C) levels. Nevertheless, HDL-raising therapies, such as cholesteryl ester transfer protein (CETP) inhibitors, failed to ameliorate cardiovascular outcomes in clinical trials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…Furthermore, our recent studies showed that FH versus control HDL contain increased isolevuglandins, which are highly reactive γ-ketoaldehydes [14], and direct modification of HDL with isolevuglandins caused a proinflammatory response to LPS. In addition to oxidation products, other factors such as LCAT, CETP, microRNAs, apoL1, and sphingosine-1-phosphate could impact the anti-inflammatory function of FH-HDL [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our recent studies showed that FH versus control HDL contain increased isolevuglandins, which are highly reactive γ-ketoaldehydes [14], and direct modification of HDL with isolevuglandins caused a proinflammatory response to LPS. In addition to oxidation products, other factors such as LCAT, CETP, microRNAs, apoL1, and sphingosine-1-phosphate could impact the anti-inflammatory function of FH-HDL [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concentration of HDL cholesterol increased significantly after ovariectomy and increased even further if ovariectomy was followed by estradiol substitution. It should be noted, that neither in human plasma serum/plasma concentration of HDL cholesterol exactly reflect structure or mechanisms of the real metabolic activity of HDL particles [ 39 ]. In addition, in rodents HDL cholesterol could play different roles than in humans [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some traditional Chinese medicines such as Polygonum cuspidatum that may consist of components with efficacy against COVID-19 have been examined in clinical trials [105]. The pro-inflammatory metabolites of arachidonic acid (AA) and eicosapentaenoic acid (EPA) such as leukotrienes and thromboxanes promote inflammation, whereas lipoxins, resolvins, protectins and maresins derived from AA, EPA and DHA facilitate wound healing, promote phagocytosis of macrophages and other immunocytes and decrease microbial load [106]. It is implicated that these unsaturated fatty acids and pro-inflammatory metabolites may serve as endogenous anti-viral compounds.…”
Section: Application Of Anti-viral Natural Products For Treatment Of mentioning
confidence: 99%